1973
DOI: 10.1021/j100628a006
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of carbon trioxide (-) radicals generated in the flash photolysis of carbonatoamine complexes of cobalt(III) in aqueous solution

Abstract: The flash photolysis of C O ( N H~)~C O~+ in aqueous solution generates the C03-radical which is characterized by its absorption spectrum with A, , , 600 nm and its second-order decay kinetics. The radical is also generated from Co(NH3)&03+ and, to a lesser extent, from Co(en)zC03+. By monitoring the decay of the C03-absorption as a function of the concentration of added scavenger solutes, values of k(CO3-+ S) have been obtained for some organic and inorganic solutes. In particular, k(C03-+ indole-3-propionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
2

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(50 citation statements)
references
References 3 publications
(4 reference statements)
6
36
0
2
Order By: Relevance
“…This indicates that either the proton hyperfine splitting constant of the carbonate radical is lower than 1 G or that the species is not protonated (see Reaction 11) over the studied pH range of 6 -9. Although the literature contains conflicting evidence regarding the protonated state of the carbonate radical over the 6 -12 pH range (36,37), recent studies by time resolved RAMAN spectroscopy have found no evidence for its protonation at pHs between 7.5 and 12.3 (38). These studies are in agreement with our EPR data indicating that the radical is not protonated at physiological pHs.…”
Section: Table I Epr Parameters Of the Carbonate Radical In Various Msupporting
confidence: 89%
“…This indicates that either the proton hyperfine splitting constant of the carbonate radical is lower than 1 G or that the species is not protonated (see Reaction 11) over the studied pH range of 6 -9. Although the literature contains conflicting evidence regarding the protonated state of the carbonate radical over the 6 -12 pH range (36,37), recent studies by time resolved RAMAN spectroscopy have found no evidence for its protonation at pHs between 7.5 and 12.3 (38). These studies are in agreement with our EPR data indicating that the radical is not protonated at physiological pHs.…”
Section: Table I Epr Parameters Of the Carbonate Radical In Various Msupporting
confidence: 89%
“…The carbonate radical is characterized by a relatively high one‐electron reduction potential (1.59 V vs NHE [69]) but is generally much less reactive and more selective than · OH. Uncertainty has long existed whether its conjugated acid, the bicarbonate radical, could be important at pH values usually occurring in natural waters (its p K a was indirectly estimated to be 9.6 [70] and 7‐8.2 [71]), but a recent pulse‐radiolysis study provided convincing evidence that the bicarbonate radical's p K a is less than 0 [72]. Therefore, we will consider only the carbonate radical.…”
Section: Qsars Of Oxidants In Aqueous Solutionmentioning
confidence: 99%
“…[2] with the permission of IUBMB). The methods include the radiolysis of solid salt matrices and aqueous solutions, oxidation of HCO 3 − by the sulfate radical anion, photolysis of carbonatoamine complexes, and flash photolysis of carbonate solutions [25][26][27][28][29][30][31]. 3.…”
Section: Oxidative Damagementioning
confidence: 99%